2015
DOI: 10.1016/j.chemosphere.2015.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure of the isopod Porcellionides pruinosus to nickel: Costs in the energy budget and detoxification enzymes

Abstract: Terrestrial isopods from the species Porcellionides pruinosus were exposed to the maximum allowed nickel concentration in the Canadian framework guideline (50 mg Ni/kg soil) and to 5× this concentration (250 mg Ni/kg soil). The exposure lasted for 28 days and was followed by a recovery period of 14 days where organisms were changed to clean soil. Organisms were sampled after 24 h, 48 h, 96 h, 7 days, 14 days, 21 days, and 28 days of exposure, and at days 35 and 42 during the recovery period. For each sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 64 publications
4
18
0
Order By: Relevance
“…[20,25]). Recently, our group has addressed the response of terrestrial isopods to long-term Ni exposure by measuring changes in energy reserves and the activity of detoxification enzymes [12]. This study confirmed the induction of oxidative stress and further revealed that other modes of action should be responsible for Ni toxicity, thus calling for a more detailed understanding of Ni effects at the molecular level.…”
Section: Hnmrmetabolomicsmentioning
confidence: 65%
See 4 more Smart Citations
“…[20,25]). Recently, our group has addressed the response of terrestrial isopods to long-term Ni exposure by measuring changes in energy reserves and the activity of detoxification enzymes [12]. This study confirmed the induction of oxidative stress and further revealed that other modes of action should be responsible for Ni toxicity, thus calling for a more detailed understanding of Ni effects at the molecular level.…”
Section: Hnmrmetabolomicsmentioning
confidence: 65%
“…In particular, the metabolome was found to change in a dynamic, non-linear way with time and dose, showing, for most metabolites, distinct patterns between the initial and later time points tested (4 and 7/14 days). Interestingly, the mortality recorded in a parallel experiment using the same time points and doses [12] showed a similar number of dead animals in control and exposed conditions at day 4, but a significant increase in mortality upon Ni exposure for 14 days. It is thus likely that the metabolic profile characterizing the short-term (4 days) response to Ni reflects the ability of terrestrial isopods to cope with soil contamination.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations